Religiosidade, etnicidade e educação: a presença das Irmãs Carlistas-Scalabriniana no Rio Grande do Sul (1915-1948) - Matiello, Marina (My University, 2019)
The aim of this study is to analyse how the Carlista-Scalabrinian education in Rio Grande do Sul (RS) state was established after the insertion of the São Carlos Borromeo – Scalabrinian Sisters Congregation in the State, considering the relationship between religiosity, ethnicity and schooling. The historical implantation process of Scalabrinian school institutions in RS was assessed and the principles of Scalabrinian mission and education related to ethnicity, religiosity and schooling was shown. It employed theoretical-methodological assumptions of cultural history and of educational history through the use of oral history and historical documentary analysis. The time frame was delimited from 1915, year of the Congregation insertion in the Italian Colonial Region (ICR) - RS, until 1948, when educational projects were developed in southern RS, in Santa Vitória do Palmar, which produced a new configuration for the congregation in the RS. The search for documents and subjects to understand the constitution and organization of the Carlist-Scalabrinian congregation and education was carried out through meetings in the General House in Rome (Italy), in the provincial houses located in Piacenza (Italy) and in Sao Paulo and Caxias do Sul (Brazil) and also in school institutions in Caxias do Sul, Guaporé, Bento Gonçalves and Farroupilha (Brazil). The results showed a Congregation marked by the triad of italianity, catholicity and education. The actions of the Carlist-Scalabrinian Sisters were constituted in daily practice through practical experiences. The education promoted in the congregation schools was focused in the development of catholic moral values, discipline and instructions, preparing, especially the female public for the good performance of household activities or for the religious vocation. The thesis is that the Congregation of Missionary Sisters of São Carlos Borromeo — Scalabrinians was built from the necessity of its founder, Giovanni Battista Scalabrini, to protect the italian migrants, to maintain the catholic faith, thus encouraging the maintenance of italian culture. The Congregation offered assistance to migrants, especially for the italians, in the area of education, health and pastoral care. The education had as its main reference the founder himself and it was composed in practice and focused in catholicity, ethnicity and schooling. Ethnicity represented an important mark of the Congregation, thus producing an identification with immigrants and their descendants. Schooling was seen as instruction of the basic fundamentals of reading, writing and calculations, while catholicism were part of the daily practices and celebrations of the Congregation schools.
O estudo é desenvolvido com o objetivo de analisar como se constituiu a educação carlista-scalabriniana no Rio Grande do Sul, a partir da inserção da Congregação das Irmãs de São Carlos Borromeo – Scalabrinianas no Estado, considerando a relação religiosidade, etnicidade e escolarização. Para tal, busca-se investigar o processo histórico de implantação de instituições escolares scalabrinianas no Rio Grande do Sul e apresentar os princípios da missão e da educação scalabriniana em relação com a etnicidade, a religiosidade e a escolarização. Utilizam-se pressupostos teórico-metodológicos da história cultural e da história da educação, com o emprego da história oral e da análise documental histórica. O recorte temporal foi delimitado de 1915, ano de inserção da Congregação na Região Colonial Italiana (RCI) — RS, até 1948, quando iniciaram as obras educacionais no Sul do estado do RS, em Santa Vitória do Palmar, o que produz uma nova configuração para a organização da congregação no estado gaúcho. O percurso da pesquisa é marcado pela busca de documentos e da contribuição de sujeitos para compreender a constituição e a organização da congregação e da educação carlistascalabriniana. Para tal, visitou-se a Casa-Geral — em Roma/Itália — e as casas provinciais localizadas em Piacenza — Itália e no Brasil — São Paulo e Caxias do Sul. Instituições escolares também foram visitadas no Rio Grande do Sul, nos Municípios de Caxias do Sul, Guaporé, Bento Gonçalves e Farroupilha. O resultado aponta para uma congregação marcada pela tríade: italianidade, catolicidade e educação. As ações das Irmãs Carlistas-Scalabrinianas foram se constituindo no fazer cotidiano, através de experiências práticas. A educação, promovida nas escolas da congregação, tinha como foco o desenvolvimento de valores morais católicos, a disciplina e a instrução, preparando, especialmente o público feminino, para o bom desempenho de atividades do lar ou para a vocação religiosa. A tese é a de que a Congregação das Irmãs Missionárias de São Carlos Borromeo — Scalabrinianas foi construída a partir da necessidade de seu fundador, Giovanni Battista Scalabrini, de tutelar os migrantes italianos, para que mantivessem a fé católica e, para isso, estimulou a manutenção da cultura italiana. A congregação ofereceu assistência aos migrantes, especialmente italianos, na área da educação, da saúde e da pastoral. A educação tinha como principal referência o próprio fundador, era constituída na prática e estava voltada à catolicidade, à etnicidade e à escolarização. A etnicidade representava uma marca importante da congregação, com a qual se produzia uma identificação com os imigrantes e seus descentes; a escolarização era entendida como instrução de fundamentos básicos de leitura, escrita e cálculo; e o catolicismo aparecia nas práticas cotidianas e nas celebrações das escolas da congregação.
Keywords: Scalabrinianas - Educação; Religiosidade; Unidade cristã; Educação; Scalabrinianas - Education; Religiousness; Christian union; Education